Wherefrom Comes the ‘Pregnant Widow’? An Old Russian Source for the Author of “From the Other Shore” - Gonneau, Pierre (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The aim of the paper is to find the historical or literary prototype of the ‘pregnant widow’ described by Alexander Herzen in his collection of essays ‘From the Other Shore’ (1849−1850). The following possible sources are considered. The duchess of Berry Marie-Caroline gave birth to Henri Charles d’Artois, count of Chambord, on the 19th September 1820, almost eight months after a Bonapartist by the name of Louvel had killed her husband. But the child, last heir of the elder line of the French Bourbons, never reigned. In Russian history, the fate of Tsar Ivan VI (proclaimed in 1740) and his mother offers a parallel, but only partly fits the story of the pregnant widow. The episode of the ‘sinful birth’ of Svyatopolk the Accursed Prince in ‘The Tale of Bygone Years’ (‘The Russian Primary Chronicle’) so perfectly corresponds with what Herzen describes that it can be identified as the author’s – conscious or unconscious – source.